Description of Nutritional Status with The Development of Toddlers at The Working Area of Public Health Center of Wates, Lampung Province, Indonesia - Kumalasari, Desi; Sagita, Yona Desni; Veronica, Septika Yani (Universitas Aisyah Pringsewu, 2021)
Stunting describes chronic malnutrition status during growth and development since early life. This situation is represented by a z-score of height for age less than -2 standard deviations based on growth standards according to the World Health Organization. The method used in this research was a quantitative research method with a descriptive type of research objective to describe the Nutritional Status of Toddlers Age 12-59 Months at the working area of the Public Health Center in Wates. The population in this research were toddlers age 12-59 months totaling 1314 toddlers. The sampling technique used quota sampling with the number of samples obtained as many as 100 toddlers, the instrument in this research used an observation sheet, namely research obtained directly from the source in the form of interviews, polls from individuals or groups (people) as well as observations from an object, the genesis or test results (objects). Frequency distribution of nutritional status of 100 toddlers obtained normal nutritional status 76 (76%) toddlers respondents, 11 (11%) toddlers respondents with short nutritional status, 8 (8%) toddlers respondents with nutritional status very short, and 5 (5%) toddlers respondents with high nutritional status. The distribution of the developmental frequency of toddlers from 100 toddlers obtained 95 (95%) toddlers respondents with development according to their age, 5 (5%) toddlers respondents with dubious development, and no toddlers respondents suffer deviations in their development.Stunting menggambarkan status gizi kurang yang bersifat kronik pada masa pertumbuhan dan perkembangan sejak awal kehidupan. Keadaan ini dipresentasikan dengan nilai z-score tinggi badan menurut umur (TB/U) kurang dari -2 standar deviasi (SD) berdasarkan standar pertumbuhan menurut WHO. Metode yang digunakan dalam penelitian ini adalah metode penelitian kuantitatif dengan jenis penelitian deskriptif yang bertujuan untuk mengambarkan Status Gizi Dengan Perkembangan Balita Usia 12 – 59 Bulan Di Wilayah Kerja Puskesmas Wates. Populasi dalam penelitian ini adalah balita usia 12-59 bulan yang berjumlah 1314 balita. Tehnik pemngambilan sampel mengunakan quota sampling dengan jumlah sampel yang didapatkan sebanyak 100 balita, instrumen dalam penelitian ini menggunakan lembar observasi yaitu penelitian yang diperoleh secara langsung dari sumber aslinya yang berupa wawancara, jajak pendapat dari individu atau kelompok (orang) maupun hasil observasi dari suatu obyek, kejadian atau hasil pengujian (benda). Distribusi frekuensi status gizi dari 100 balita didapatkan tatus gizi normal 76 (76%) responden balita, 11 (11%) responden balita dengan status gizi pendek, 8 (8%) responden balita dengan status gizi sangat pendek dan 5 (5%) responden dengan status gizi tinggi. Distribusi frekuensi perkembangan balita dari 100 balita didapatkan 95 (95%) responden balita dengan perkembangan yang sesuai dengan umurnya, 5 (5%) responden balita dengan perkembangan yang meragukan, dan tidak ada responden balita yang mengalami penyimpangan dalam perkembangannya.